Virilization and abdominal mass in a newborn female: A case report - Natalie A. Drucker, MD; Brian W. Gray, MD; Johanna Askegard-Giesmann, MD (Elsevier, 2017)
We describe virilization in a newborn female secondary to bilateral congenital juvenile granulosa cell tumor (JGCT). The patient presented with abdominal mass and ambiguous genitalia at birth, and bilateral ovarian masses were discovered on further imaging. The patient underwent bilateral salpingo-oophorectomy in staged procedures, as it became apparent that we could not spare the ovaries. Diagnosis of JGCT was confirmed by surgical pathology. She required no adjuvant therapy and has no signs of recurrence at two-year follow-up.